Analysis of composite material properties and their possibilities to use them in bus frame construction - Pravilonis, Tautvydas; Sokolovskij, Edgar (Transport, 2020)
Energy consumption and the emission of harmful particles have increased significantly in recent decades. The constant development of transport poses an increasing threat to the environment. The search for alternative energy-saving solutions is closely linked to the development and improvement of new vehicles, reducing their negative impact on the environment. Fiberglass or carbon fiber are among the most promising materials that can reduce weight in all types of vehicles. They are also much easier to recycle than steel. Fiberglass or carbon fiber composite materials are widely used in a variety of applications: construction, ships, and trains. Vehicles and buses are no exception. These innovative materials are used not only for interior elements but also in constructional units for the production of light duty vehicles. Meanwhile in buses these material are not yet used in safety frame. Bus safety frames are made out of steel. Therefore, in this work the fiberglass composite material from which the tubes are made by pultrusion process would replace the steel tube in the safety frame construction of the bus. Such technology could reduce the weight of the bus safety frame by about 20%. Other parameters would also be affected by weight reduction: safety: bus would be less overloaded, the braking distance would be reduced, the center of gravity position would be closer to the ground; environmental: lower air pollution due to lower CO2 emissions; economic: lower fuel consumption. However, before using such technology, it is necessary to determine the properties of the composite material. Properties were determined by tensile and shear tests (ISO 527-2:2012 and ASTM D5379/D5379M-19). Comparison tests of different materials (tensile and crushing tests) were also performed. According to the experimental results, conclusions were drawn regarding the possibility of using fiberglass for the bus frame. First published online 1 July 2020